Will the Real Immunogens Please Stand Up: Exploiting the Immunogenic Potential of Cryptococcal Cell Antigens in Fungal Vaccine Development - Samantha L. Avina; Siddhi Pawar; Amariliz Rivera; Chaoyang Xue (Journal of Fungi)
Cryptococcus neoformans is an opportunistic fungal pathogen that is a continuous global health concern, especially for immunocompromised populations. The World Health Organization recognized C. neoformans as one of four critical fungal pathogens, thus emphasizing the need for increased research efforts and clinical resource expansion. Currently, there are no fungal vaccines available for clinical use. Exciting new findings in cryptococcal vaccine development have identified whole cell-based and subunit-based vaccinations to help mitigate health risks and make commercialization attainable. Importantly, recent work has focused on how different cryptococcal cell-wall antigens modified in these vaccine candidates allow us to manipulate their immunogenicity to produce a desired long-term protective anti-fungal immune response. In this review, we discuss the different cryptococcal cell immunogens, namely the polysaccharide capsule, glucans, chitin/chitosan, mannoproteins, and extracellular vesicles, and their role in novel cryptococcal vaccination approaches. Additionally, we examine the immunological mechanisms responsible for protection in these vaccine candidates and the similar host response-stimulation pathways induced through different immunogen exposure.